2015
DOI: 10.1007/s00253-015-6644-8
|View full text |Cite
|
Sign up to set email alerts
|

Fruit peels support higher yield and superior quality bacterial cellulose production

Abstract: Fruit peels, also known as rinds or skins, are wastes readily available in large quantities. Here, we have used pineapple (PA) and watermelon (WM) peels as substrates in the culture media (containing 5 % sucrose and 0.7 % ammonium sulfate) for production of bacterial cellulose (BC). The bacterial culture used in the study, Komagataeibacter hansenii produced BC under static conditions as a pellicle at the air-liquid interface in standard Hestrin and Schramm (HS) medium. The yield obtained was ~3.0 g/100 ml (on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…Hence, the use of pineapple peel waste can be explored in effective bioproduct generation. Kumbhar et al (2015) reported higher amount of bacterial cellulose production (0.3 g/g) from pineapple peel. Besides, several authors have made an attempts to use pineapple peel as a substrate for production of bromelain, polyphenols (Gautam et al, 2010), biohydrogen, and biogas (Nga and Trang, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Hence, the use of pineapple peel waste can be explored in effective bioproduct generation. Kumbhar et al (2015) reported higher amount of bacterial cellulose production (0.3 g/g) from pineapple peel. Besides, several authors have made an attempts to use pineapple peel as a substrate for production of bromelain, polyphenols (Gautam et al, 2010), biohydrogen, and biogas (Nga and Trang, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…24 The sharp peaks in the XRD pattern of native BC indicate that the cellulose produced by K. hansenii MCM B-967 is highly crystalline. 13 In the present study of BC-HA, additional peaks observed at 10.6°, 27.2°, 31.8°, 40.5°, 45.6°, and 56.6° could be assigned to HA crystals formed due to the activation of BC by Ca 2+ , followed by mineralization in 1.5× SBF. The decrease in the intensity of characteristic peaks of cellulose in the nanocomposite indicates that HA (ICDD-PDF file number 9-432) is the dominating component of the composite.…”
mentioning
confidence: 80%
“…13 Briefly, a single colony of Komagataeibacter hansenii MCM B-967 was inoculated into 100 mL pineapple peel medium and incubated at an ambient temperature (25°C±3°C) under static conditions. After 2 days of incubation, 10% of inoculum was transferred to 100 mL pineapple peel medium and further incubated for 7 days under static conditions at the ambient temperature (25°C±3°C).…”
Section: Experimental Section Production Of Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications involve the production of different compounds, such as: antioxidant phenols (Nor Halaliza & Zulkifly, 2017;Alias & Abbas, 2017), acids (Tang et al, 2014;Lun et al, 2014), wine/vinegar (Roda et al, 2017;Praveena & Estherlydia, 2014), bacterial cellulose. (Kumbhar et al, 2015), acetone-butanolethanol (ABE) using Clostridium acetobutylicum McCoy et al Emend. Keis et al(Khedkar et al, 2017), hydrogel (Dai & Huang, 2016), phenolic antioxidants using Rhizopus oligosporus Saito (Correia et al, 2004), yellowish orange pigment from Chryseobacterium artocarpi Venil et al 2014(Aruldass et al, 2016.…”
Section: Other Applicationsmentioning
confidence: 99%